THE USE OF VISUAL MEDIA AS ONE ALTERNATIVE TO IMPROVE STUDENTS' LEARNING MOTIVATION - Kristina, Marilin; Septia Nagara, Erliza (JECE (Journal of Ethics and Character Education), 2023)
The use of visual media serves to convey messages through images that involve the sense of sight. The messages conveyed are expressed through symbols of visual communication. Visual media aims to capture attention, clarify material, and illustrate facts and information. The problem addressed in this research is the low learning motivation of fourth-grade students at SD Negeri 3 Sendang Mulyo in social studies (IPS) learning. The purpose of this study is to enhance the learning motivation of fourth-grade students at SD Negeri 3 Sendang Mulyo in IPS learning by using visual media. The research method employed is Classroom Action Research, consisting of 2 cycles, with each cycle comprising 4 stages: planning, implementation, observation, and reflection. Based on the research findings, it can be concluded that the implementation of learning using visual media can enhance students' learning motivation in social studies for fourth-grade students at SD Negeri 3 Sendang Mulyo